Plan de marketing para reactivar el sector turístico de la ciudad creativa Portoviejo post covid-19 - Rendón Giler, Andrea Lilibeth (2022)
The objective of this research was to design a marketing plan for the reactivation of the tourism sector in Portoviejo canton. In the first phase, the development of the situational diagnosis was carried out to identify the current conditions of the postcovid-19 tourism sector in Portoviejo, in the second a market study was carried out to analyze supply, demand and competition, finally, structured improvements for the promotion or dissemination of the tourist attractions and resources of the destination. It was observed that the destination has deficiencies in the use of bio-protocols to provide security to tourists through the service provided. The evaluation of the offer allowed to establish the potentiality of the tourist attractions, determined 12 with a high level and 10 with an emerging level; the results of the survey showed that the demand is mainly interested in visiting archaeological sites; in the analysis of the competition, it was found that the main competitors of the destination are Manta and Puerto López. Finally, strategies were established under the 4P approach of the marketing mix (5 directed to the product, 3 related to the price, 3 in relation to the place and 5 around the promotion), made up of 13 projects that seek to promote the use of technological tools for the positioning of Portoviejo. In conclusion, the Creative City of UNESCO Portoviejo has ideal characteristics to achieve tourism development, but requires better marketing management.